Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

heydayana

  • 3 years ago

solve for x: ln(x^2 +1) - 3lnx= ln2?

  • This Question is Closed
  1. Umangiasd
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    3lnx=ln(x^3) then by the propertie lna-lb=ln(a/b) ln((x^2+1)/x^3)=ln2 That means (x^2+1)/x^3 = 2 then solve that, x=1

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy